Employability of students in "Library and Information Management" - Yankova, Ivanka; Stancheva, Silvia; Vasileva, Rumelina; Dimitrova, Tzvetelina (Qualitative and Quantitative Methods in Libraries; Vol 5 No 3 (2016): September 2016 Issue, 2017)
The scientific report presents the development of the project "Investigation and analysis of the opportunities for professional development of students of" Library and Information Management". The project aims to stimulate interest in the opportunities for real career development and to increase the motivation of students and doctoral students to participate and perform field research and practice. Surveys of the students will take place under the guidance of professors from ULSIT and leading professionals in various areas of information and communication activities. It presents opportunities to enhance information literacy and competence of students which the University of Library Studies and Information Technologies in Sofia, Bulgaria, in particular the Department of Library Management provides them.